Research on Incentive Mechanism of Millennials in Chinese Bank - Xie, J.H. (2022)
The first driving force for bank development and the first influencing factor for bank rise and fall is how to attract and retain talent. How to attract and hold talent is the key issue for the development of banks. With the great changes of the times, banks have gradually revealed some problems with staff motivation, such as recruitment difficulties, high turnover rate, low motivation, etc. At this stage, the incentive mechanism for young employees is defective and cannot play a good role in motivating employees. The millennial generation employees account for a high proportion of the bank and are the backbone of the bank's operation, and their massive loss or slack work is extremely detrimental to the normal operation and development of the bank. Therefore, how to motivate young employees and establish an efficient incentive mechanism for young employees is the core issue of the current research on incentive mechanisms in the Chinese banking industry.